THE UNIQUE CHARACTERISTICS OF THE PSYCHOLOGY OF LEADER CHARACTERS IN ABDULLA QODIRIY’S NOVEL “O‘TKAN KUNLAR” (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2024)
This article discusses certain characteristics of the leader characters portrayed in Abdulla Qodiriy’s novel O‘tkan Kunlar.